Industry-and occupation-specific skills of displaced workers - Lagoa, S. (2014)
The role of marketable skills of workers has been the core focus of the human capital framework. Individuals accumulate skills that enhance their productivity and earnings, but sometimes they are forced to change their professional careers and find new jobs. This paper uses Portuguese linked employer-employee data – Quadros de Pessoal - and explores the relevance of industry and occupation specific skills by looking at the wage losses of displaced workers due to firms shutting down. Our empirical analysis considers the four alternatives that workers face after displacement namely changing both industry and occupation; changing industry and staying in the same occupation; changing occupation but staying in the same industry, or staying in the same industry and occupation. Empirical evidence suggests that for workers who switch industry/occupation, pre-displacement industry/occupation tenure implies a larger wage loss than for industry/occupation stayers. In a context of rising unemployment, our analysis allows us to suggest that when experienced workers are displaced and forced to find a job in a different industry, they suffer considerable wage cuts.